Structure of a mutagen from roasted seeds of Moringa oleifera - Villasenor, Irene M (Archīum Ateneo, 1989)
A mutagenic compound was isolated from roasted seeds of Moringa oleifera Lam. Its structure has been elucidated by spectral analysis as 4(α-L-rhamnosyloxy)phenylacetonitrile. The results of the Micronucleus Test, an in vivo method, showed that the number of micronucleated polychromatic erythrocytes (PCE)/1000 PCE for this compound is higher than that of the solvent control, dimethylsulfoxide, and approximates that of the positive control, tetracycline. This indicates that 4(α-L-rhamnosyloxy)phenylacetonitrile is a genotoxic compound.